2005
DOI: 10.1161/01.str.0000181755.23914.53
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Caregiving Burden and Quality of Life in Caregivers of Stroke Patients

Abstract: Background and Purpose-A large proportion of disabled stroke survivors live at home and are supported by informal caregivers. Identification of determinants of caregiver burden will help to target caregiver interventions. Methods-Data on patient, caregiver, and health and social support characteristics were collected prospectively over 1 year in 232 stroke survivors in a randomized trial of caregiver training. The contribution of these variables to caregiver burden score (CBS) and quality of life (QOL) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
345
9
30

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(420 citation statements)
references
References 30 publications
26
345
9
30
Order By: Relevance
“…Training caregivers in the basic skills of moving and handling a patient, activi ties of daily living and simple nursing tasks can reduce the burden of care, enhance caregiver's quality of life and reduce the risk of injury to caregivers and patients (McCullagh et al 2005;Pierce et al 2007;Hinojosa and Rittman 2009). In the current study the majority of caregivers expressed a need for more training in physical handling skills.…”
Section: Discussionmentioning
confidence: 99%
“…Training caregivers in the basic skills of moving and handling a patient, activi ties of daily living and simple nursing tasks can reduce the burden of care, enhance caregiver's quality of life and reduce the risk of injury to caregivers and patients (McCullagh et al 2005;Pierce et al 2007;Hinojosa and Rittman 2009). In the current study the majority of caregivers expressed a need for more training in physical handling skills.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature pertaining to caregiving following stroke, caregiver training was found to lessen the impact of age and severity of illness on caregiver burden and quality of life, underscoring the importance of these programs for informal caregivers. 38 Future work may focus on the experience of caregiver burden and interventions that alleviate the impact of caring on caregivers of individuals with SCI.…”
Section: Interventions On Caregivingmentioning
confidence: 99%
“…In the face of this scenario, studies have shown that the compromising of cognitive function, presence of depression and problems of memory or functional capacity in patients following stroke worsen the overload of family carers (2)(3) .…”
Section: Introductionmentioning
confidence: 99%